Elevated systemic TGF-β impairs aortic vasomotor function through activation of NADPH oxidase-driven superoxide production and leads to hypertension, myocardial remodeling, and increased plaque formation in apoE−/− mice - Buday, Anna; Őrsy, Petra; Godó, Mária; Mózes, Miklós; Kökény, Gábor; Lacza, Zsombor; Koller, Ákos; Ungvári, Zoltán; Groß-Weissmann, Marie-Luise; Benyó, Zoltán; Hamar, Péter (American journal of physiology. Heart and circulatory physiology, 2010)
The role of circulating, systemic TGF-β levels in endothelial function is not clear. TGF-β1 may cause endothelial dysfunction in apolipoprotein E-deficient (apoE−/−) mice via stimulation of reactive oxygen species (ROS) production by the NADPH oxidase (NOX) system and aggravate aortic and heart remodeling and hypertension. Thoracic aorta (TA) were isolated from 4-mo-old control (C57Bl/6), apoE−/−, TGF-β1-overexpressing (TGFβ1), and crossbred apoE−/− × TGFβ1 mice. Endothelium-dependent relaxation was measured before and after incubation with apocynin (NOX inhibitor) or superoxide dismutase (SOD; ROS scavenger). Superoxide production within the vessel wall was determined by dihydroethidine staining under confocal microscope. In 8-mo-old mice, aortic and myocardial morphometric changes, plaque formation by en face fat staining, and blood pressure were determined. Serum TGF-β1 levels (ELISA) were elevated in TGFβ1 mice without downregulation of TGF-β-I receptor (immunohistochemistry). In the aortic wall, superoxide production was enhanced and NO-dependent relaxation diminished in apoE−/− × TGFβ1 mice but improved significantly after apocynin or SOD. Myocardial capillary density was reduced, fibrocyte density increased, aortic wall was thicker, combined lesion area was greater, and blood pressure was higher in the apoE−/− × TGFβ vs. C57Bl/6 mice. Our results demonstrate that elevated circulating TGF-β1 causes endothelial dysfunction through NOX activation-induced oxidative stress, accelerating atherosclerosis and hypertension in apoE−/− mice. These findings may provide a mechanism explaining accelerated atherosclerosis in patients with elevated plasma TGFβ1.